Epithelial thickness mapping: mechanical photorefractive keratectomy versus transepithelial photorefractive keratectomy - Ahmed F El-Shahed; Reem F El-Shahed; Karim A Gaballah (Delta Journal of Ophthalmology, 2022)
Aim The aim of this study was to compare mechanical photorefractive keratectomy (PRK) to transepithelial photorefractive keratectomy (tPRK), used to correct mild and moderate myopia, with respect to the epithelial thickness mapping (ETM). Setting The study was carried out at Al-Mashreq Eye Center, Cairo, Egypt. Patients and methods This is a prospective comparative study that was carried out on 20 myopic patients (40 eyes), with spherical equivalent (SE) ranging from −1.0 to −5.0 D. The cases were divided into two groups: group A included the right eyes (OD) of all patients, and group B included the left eyes (OS). Group A underwent mechanical PRK using ‘hockey stick’ and excimer laser, using Mel-90 excimer laser with 250 Hz mode, and 0.7-mm spot scanning. Group B underwent tPRK using Mel-90 (8-mm lamellar ablation for 55 μm, 250 Hz). Uncorrected visual acuity (UCVA), manifest refraction, and ETM using AngioVue spectral domain optical coherence tomography systems were performed. The ETM was measured preoperatively and at 1 week, 1 month, and 3 months postoperatively. In addition, postoperative pain was assessed. Results The median preoperative UCVA was 0.3 (range, 0.2–0.4) in both eyes (OU), whereas the median preoperative best-corrected visual acuity was 1 (range, 0.8–1). There was a statistically significant increase in UCVA across the postoperative period in both groups (P<0.001). The median UCVA improved to 0.5 (OU) after 1 week, and to 0.9 (OD) and 1.0 (OS) after 1 month and remained almost the same at 3 months postoperatively. There was a statistically significant decrease in SE at all points of the follow-up period in both groups (P<0.001). A slight change in SE was observed between the first and third month postoperatively in both groups, which was statistically insignificant. Patients reported postoperative pain on the first postoperative day, which was more in the tPRK group. There was a statistically significant change in epithelial thickness across the study period in both groups (P<0.001). The ETM showed a faster epithelial regeneration in group B, which was statistically significant at 1 week postoperatively (P=0.004). The epithelial thickness continued to increase in both groups to reach almost the preoperative value at the third month postoperatively. All cases that showed postoperative haze were less than grade 1.0 (Hanna’s scale). Conclusion Mechanical PRK and tPRK provided very similar results 3 months postoperatively. Both procedures were predictable, effective, and safe. The patients reported postoperative pain on the first postoperative day that was more in the tPRK group. The tPRK group expressed a faster epithelial regeneration than the PRK group at 1 week postoperatively. However, at 3 months postoperatively, the corneal epithelium reached an almost normal thickness in both groups. Visual recovery was noted to be faster in the tPRK group.